Chemical Immunology and Allergy 2005
DOI: 10.1159/000087913
|View full text |Cite
|
Sign up to set email alerts
|

TNF-&agr;-Mediated Stress-Induced Early Pregnancy Loss:A Possible Role of Leukemia Inhibitory Factor

Abstract: Data presented in the this review suggest LIF as a good candidate for further studies addressing molecular mechanisms underlying stress-induced early embryonic death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…A third possible pathway is through hormone regulation. The elevated estrogen level is associated with pathogenesis of ICP . The disease is more common in multiple than singleton pregnancies (20.9% vs 4.7%) .…”
Section: Discussionmentioning
confidence: 99%
“…A third possible pathway is through hormone regulation. The elevated estrogen level is associated with pathogenesis of ICP . The disease is more common in multiple than singleton pregnancies (20.9% vs 4.7%) .…”
Section: Discussionmentioning
confidence: 99%
“…Some results from our work and investigations addressing the functional role of leukemia inhibitory factor (LIF) (see Torchinsky et al, 2005 for references) imply that the cytokine is a good candidate for studies addressing this topic. As to the mechanisms which TNF␣ might engage to act as a teratological protector, convincing evidence suggested that those might be associated with the transcription factor NF-B (see Torchinsky and Toder, 2004 for references).…”
Section: Tnf␣ and Nf-bmentioning
confidence: 91%
“…At high concentrations, TNF can upregulate cell adhesion molecules, disrupt cytoskeletal organization, impair tight junction protein functions, and increase the paracellular permeability of the BBB (Pan et al 1997). Studies in uterine cells have suggested that TNF may affect LIF signaling, and contribute to stress-induced early embryonic death (Torchinsky et al 2005). This raises the questions of whether and how TNF modulates the response of the cerebral endothelial cells to LIF, as both cytokines show increased circulating concentrations in inflammation.…”
Section: Introductionmentioning
confidence: 99%